Culture-related Content in an EFL Textbook: A Need for Locally Relevant Materials - Rudi Hartono (LINGUA: Jurnal Bahasa dan Sastra, 2017)
Abstract: This study aimed to shed light on the representations of global and local cultures in an EFL textbook. The analysis of cultural themes of the local English textbook was described qualitatively. The textbook was analyzed in terms of its cultural contents in order to examine how the representations of foreign, local and global cultures are portrayed in this textbook. The study also looked into the degree and ways in which the authors’ resistance toward English culture as the target culture in this textbook. The analysis revealed that cultural content in this textbook is dominated by local cultures. The textbook authors attempt to instill local values in this textbook in order to provide students with more meaningful locally relevant materials. The study also suggests that EFL local textbooks should ideally include both global culture and local culture in order to equip students with diverse learning experience and better intercultural learning. Keywords: EFL textbook, culture-related content, and locally relevant materials. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan representasi budaya global dan lokal dalam buku teks bahasa Inggris. Hasil analisis tema-tema budaya dalam buku teks bahasa Inggris lokal ini dijelaskan secara kualitatif. Buku teks dianalisis dalam hal konten budayanya untuk melihat bagaimana representasi budaya asing, lokal dan global digambarkan dalam buku teks ini. Studi ini juga mengkaji sejauh mana cara dan resistensi penulis buku terhadap budaya bahasa Inggris sebagai budaya target dalam buku teks ini. Hasil menunjukkan bahwa konten budaya dalam buku ini didominasi oleh budaya lokal. Penulis buku berusaha untuk menanamkan nilai-nilai lokal dalam buku teks ini untuk memberikan siswa materi yang relevan secara lokal dan lebih bermakna. Studi ini juga menunjukkan bahwa buku teks Bahasa Inggris lokal idealnya harus mencakup budaya global dan budaya lokal untuk membekali siswa dengan pengalaman belajar yang beragam dan pembelajaran antar budaya yang lebih baik. Kata-kata kunci: buku teks Bahasa Inggris, konten budaya, materi lokal yang relevan